Using Rasch modeling to investigate the construct of motor competence in early childhood. (May 2016) - Utesch, Till; Bardid, Farid; Huyben, Floris; Strauss, Bernd; Tietjens, Maike; De Martelaer, Kristine; Seghers, Jan; Lenoir, Matthieu
Abstract: Purpose: The present study investigated the dimensionality and homogeneity of motor competence, which is defined as the ability that underlies the performance of a wide variety of motor skills, in early childhood using a large set of items. Method: A total of 1467 children (aged 3–6 years) were measured with the Motor Proficiency Test for 4- to 6-Year-old Children (Motoriktest für vier-bis sechsjährige Kinder [MOT 4-6]), which consists of 17 items. Results: Analyses using the Partial Credit Model and mixed Rasch model revealed a one-dimensional structure (CR = 1.964, p CR = .06; P-χ 2 = −.227, p p - χ 2 = .24 ). Due to unordered threshold parameters, five items were excluded. These items have a scoring system that counts the amount of successful trials (0–2). Conclusion: The study shows item and person homogeneity within a validated motor score, using 12 items of the MOT 4-6. Thus, it provides evidence of a single latent construct (i.e., motor competence), which underlies the performance of motor skills in early childhood. Furthermore, it shows that counting the number of successful trails may be less suitable as a scoring system in motor competence assessment. Present findings also support the use of validated composite scores in motor assessment. Highlights: A one-dimensional structure was found to underly motor assessment in early childhood. The study presents a Rasch homogeneous motor assessment in early childhood. The MOT 4-6 Short-Form consisting of 12-items is introduced. Composite scores in diagnostic assessments need to be statistically validated.